"Interpretación del recurso extraordinario de casación en material civil, vulnera la tutela constitucional" - Arana Peralta, Maritza Georgina (2014)
The present work of legal and doctrinal research was entitled "INTERPRETATION OF SPECIAL APPEAL IN CIVIL BREACH CUSTODY CONSTITUTIONAL", since misinterpretation of resources has as old as the ratio of legal professionals antecedent in Ecuador there is a gap in terms of bad legal interpretation of the extraordinary resources of Cassation, this has resulted in large number of cases that reach the National Court, filed by the parties, mainly for lack clarity and precision in the legal grounds on the grounds that creates violated. With this technical legal research aims Reforming the Art. 18 '' Law of Cassation Ecuadorian to punish those professionals who do not substantiate adequately the resources of Cassation to repair the damage caused by the delay of the implementation since should be considered in the Civil Law